AKOMODASI BUDAYA LOKAL DALAM PUTUSAN TARJIH MUHAMMADIYAH - Supardi Mursalin (Faculty of Sharia (Islamic Law) at Fatmawati Sukarno State Islamic University Bengkulu, 2018)
The cultural appreciation in Muhammadiyah seemed to be unfavorable. Muhammadiyah residents are considered to have anti-cultural tendencies, and in reality Muhammadiyah is known as a missionary movement that is very anti against popular religious cultures such as tahlilan, yasinan, and istighasah. This impression is not entirely true, because one of the institutions in Muhammadiyah, Majelis Tarjih and Tajdid, discussed religious issues that emerged in the community to find solutions, solutions or answers. The issue of the Veil in the Tarjih Muhammadiyah Decision has somewhat revealed a desire to accommodate local culture with the verdict applied. This accommodation, textually the verdict is considered still shy, but in the field in general it has adjusted to the local culture or even with the progress of civilization.